Improving the Effectiveness of Psychological Interventions for Depression and Anxiety in Cardiac Rehabilitation: The PATHWAY Research Programme Including 4 RCTs - Adrian Wells; David Reeves; Peter Fisher; Linda Davies; Gemma Shields; Patrick Joseph Doherty; Anthony Heagerty; Calvin Heal; Lindsey Brown; Lora Capobianco (NIHR Journals Library, 2024)
Background Cardiac rehabilitation improves health and quality of life and reduces risk of further cardiac events. Twenty-eight per cent of cardiac rehabilitation patients experience clinically significant anxiety and 19% suffer depression. Such patients are at greater risk of death, further cardiac events and poorer quality of life and use more health care, leading to higher NHS costs. The available psychological treatments for cardiac patients have small effects on anxiety and depression and quality of life; therefore, more effective treatments are needed. Research shows that a thinking style dominated by rumination and worry maintains anxiety and depression. A psychological intervention (metacognitive therapy) effectively reduces this style of thinking and alleviates depression and anxiety in mental health settings. The PATHWAY study evaluated two versions of metacognitive therapy applied in cardiac rehabilitation services. Objectives The primary aim was to improve psychological outcomes for cardiac rehabilitation patients. We evaluated two formats of metacognitive therapy: (1) a group-based face-to-face intervention delivered by cardiac rehabilitation staff (group-based metacognitive therapy) and (2) a paper-based, self-directed intervention (home-based metacognitive therapy). Each was compared with usual cardiac rehabilitation alone in separate randomised controlled trials. Design A randomised feasibility trial (work stream 1) and a full-scale randomised controlled trial (work stream 2) evaluated group-metacognitive therapy, while separate feasibility and full-scale trials (work stream 3 and work stream 3+, respectively) evaluated home-based metacognitive therapy. A cost-effectiveness analysis of group-metacognitive therapy was conducted, along with stated preference surveys and qualitative studies examining patient psychological needs and therapists' perspectives on metacognitive therapy. Setting Seven NHS cardiac rehabilitation services across the north-west of England. Participants Adults aged ≥ 18 years who met cardiac rehabilitation eligibility criteria, scored ≥ 8 on depression or anxiety subscales of the Hospital Anxiety and Depression Scale, and were able to read, understand and complete questionnaires in English. Interventions Work stream 1 and work stream 2 - a 6-week group-metacognitive therapy intervention delivered by cardiac rehabilitation staff plus usual cardiac rehabilitation compared with usual cardiac rehabilitation alone. Group-metacognitive therapy was delivered once per week for 6 weeks, with each session lasting 90 minutes. Work stream 3 and work stream 3+ - home-based metacognitive therapy plus usual cardiac rehabilitation compared with usual cardiac rehabilitation alone. Home-metacognitive therapy was a paper-based manual that included six modules and two supportive telephone calls delivered by cardiac rehabilitation staff. Main outcome measures The Hospital Anxiety and Depression Scale total score at 4-month follow-up was the primary outcome in all trials. A range of secondary outcomes were also evaluated. Results Our qualitative study with 46 patients across three cardiac rehabilitation services suggested that cardiac rehabilitation patients' psychological needs were not met by current approaches and that metacognitive therapy might offer an improved fit with their psychological symptoms. The internal pilot feasibility study (work stream 1; n = 54) demonstrated that a full-scale randomised controlled trial was feasible and acceptable and confirmed our sample size estimation. A subsequent full-scale, single-blind randomised controlled trial (work stream 2; n = 332) showed that adding group-based metacognitive therapy to cardiac rehabilitation was associated with statistically significant improvements on the Hospital Anxiety and Depression Scale (primary outcome) in anxiety and depression compared with cardiac rehabilitation alone at 4-month (adjusted mean difference −3.24, 95% confidence interval −4.67 to −1.81, p < 0.001; standardised mean difference 0.52) and 12-month follow-up (adjusted mean difference −2.19, 95% confidence interval −3.72 to −0.66, p = 0.005; standardised mean difference 0.33). The cost-effectiveness analysis suggested that group-metacognitive therapy was dominant, that it could be cost saving (net cost −£219, 95% confidence interval −£1446 to £1007) and health increasing (net quality-adjusted life-year 0.015, 95% confidence interval −0.015 to 0.045). However, confidence intervals were wide and overlapped zero, indicating high variability in the data and uncertainty in the estimates. A pilot feasibility trial (work stream 3; n = 108) supported a full-scale trial of home-metacognitive therapy and was extended (work stream 3+; n = 240). In the full trial, the adjusted mean difference on the Hospital and Anxiety and Depression Scale favoured the metacognitive therapy + cardiac rehabilitation arm (adjusted mean difference −2.64, 95% confidence interval −4.49 to −0.78, p = 0.005; standardised mean difference 0.38), with statistically significant greater improvements in anxiety and depression in home-metacognitive therapy plus cardiac rehabilitation than in cardiac rehabilitation alone at 4-month follow-up. A stated preference survey on clinic-delivered psychological therapy (not specific to metacognitive therapy) indicated a preference for including psychological therapy as part of cardiac rehabilitation. Participants favoured individual therapy, delivered by cardiac rehabilitation staff, with information provided prior to therapy and at a lower cost to the NHS. A pilot stated preference study focused on preferences for home- or clinic-based psychological therapy. Preferences were stronger for home-based therapy than for centre-based, but this was not statistically significant and participants highly valued receiving therapy and having reduced waiting times. Limitations Limitations include no control for additional contact as part of metacognitive therapy to estimate non-specific effects. Work stream 3+ did not include 12-month follow-up and therefore the long-term effects of home-based metacognitive therapy are unknown. The health economics analysis was limited by sample size and large amount of missing data in the final follow up. Findings from the qualitative study cannot necessarily be generalised. Conclusions Both group-based and home-based metacognitive therapy were associated with significantly greater reductions in anxiety and depression symptoms at 4 months, compared with cardiac rehabilitation alone. The results in group-based metacognitive therapy appeared to be stable over 12 months. Introducing metacognitive therapy into cardiac rehabilitation has the potential to improve mental health outcomes. Future work Future studies should evaluate the long-term effects of home-metacognitive therapy and the effect of metacognitive therapy against other treatments offered in cardiac rehabilitation. Given the uncertainty in the economic evaluation, further work is needed to determine the cost-effectiveness of metacognitive therapy. Trial registration Work stream 1/work stream 2: NCT02420431 and ISRCTN74643496; work stream 3: NCT03129282; work stream 3+: NCT03999359. The trial is registered with clinicaltrials.gov NCT03999359. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Programme Grants for Applied Research Programme (NIHR award ref: RP-PG-1211-20011) and is published in full in Programme Grants for Applied Research; Vol. 12, No. 7. See the NIHR Funding and Awards website for further award information. Plain language summary Depression and anxiety are common among cardiac rehabilitation patients. Cardiac patients with anxiety and depression are at greater risk of death, further cardiac events and poorer quality of life and use more health care, leading to higher NHS costs. Current talking-based therapies have small effects on anxiety and depression in patients with cardiovascular disease. It is important that more effective treatments for mental health are added to cardiac rehabilitation. We applied two versions of a recent treatment called metacognitive therapy in cardiac rehabilitation: a group version and a home-based (self-help) paper-based manual. The programme had three work streams conducted across seven NHS trusts.